'A COMFORTABLE LODGING AND ONE SHILLING AND FOURPENCE A DAY': THE MATERIAL BENEFITS OF AN ALMSHOUSE PLACE. (1st October 2012) - Nicholls, Angela
Abstract : This paper examines the material benefits commonly received by almshouse residents from the fifteenth to the nineteenth centuries, and attempts to assess how well off alms-people were compared with other poor people in the community. It considers not only the stipends or financial allowances received by many almspeople, but also other benefits provided, such as the accommodation, food, fuel and practical help. The evidence points to the experience of almshouse life varying a great deal, and suggests that the standard of living for many almspeople did not differ greatly from that of the poor generally. Many almspeople received poor relief; some were so poorly off that even the workhouse offered greater comfort and security. Yet, for most, there were distinct advantages to an almshouse place. Free accommodation and a regular income, no matter how small, gave them a measure of security; while their position as almshouse residents gave them status, respectability and the opportunity to benefit from further donations.